THU0326 Discontinuation and switching patterns of tumour necrosis factor inhibitor (TNFI) therapy in tnfi-naive and tnfi-experienced patients with psoriatic arthritis in the us corrona psoriatic arthritis/spondyloarthritis (PSA/SPA) registry. (12th June 2018) - Mease, P.; Liu, M.; Gershenson, B.; Hur, P.; Greenberg, J.
Abstract : Background: To better inform treatment decisions for patients with psoriatic arthritis (PsA), it is important to understand outcomes in patients who initiate a first line vs a subsequent line of TNFi therapy. Limited studies have evaluated persistence and switching of TNFi therapy in TNFi-naive vs TNFi-experienced US patients with PsA. Objectives: To examine discontinuation and switching of TNFis in TNFi-naive and -experienced patients with PsA in the US Corrona PsA/SpA Registry. Methods: All patients aged ≥18 years in the Corrona PsA/SpA Registry who were diagnosed with PsA, initiated a TNFi (index therapy) between March 2013 and, January 2017 and had ≥1 follow-up visit after TNFi initiation were included. Patients were stratified by prior TNFi use (TNFi naive: no prior TNFi or other biologic; TNFi experienced:≥1 prior TNFi). Patient demographics and clinical and disease characteristics were assessed at the time of TNFi initiation (baseline). Time to discontinuation of the index TNFi (with or without switching) and time to switch to another biologic were assessed by Kaplan-Meier analysis. Log-rank tests were used to assess differences in persistence and switching between the TNFi-naive and -experienced cohorts. Provider-reported reasons for discontinuation of the index TNFi were summarised descriptively. Results: 318 patients with PsA were included (TNFi naive, n=171; TNFi experienced, n=147), with a total follow-up of 579.2 person-years. Experienced patients had a longer mean (SD) disease duration (13.3 [10.0] vs 9.5 [9.7] years; p<0.01) and a higher proportion had a history of prednisone use (27.9% vs 17.5%; p=0.03) compared with naive patients. A total of 75 naive (43.9%) and 80 experienced patients (54.4%) discontinued their index TNFi, including 33 (19.3%) and 48 (32.7%), respectively, who switched to a new biologic. The median (95% CI) time to discontinuation of the index TNFi in naive vs experienced patients was 27 (22 to 33) vs 20 (18 to 28) months, respectively (figure 1). Among those who discontinued their TNFi, the mean (SD) time to discontinuation was 14.5 (8.0) months in naive patients vs 14.0 (8.9) months in experienced patients. Due to the low number of switching events, the median time to switch of the index TNFi could not be estimated. Among those who switched to a new biologic, the mean (SD) time to switch was 16.0 (8.1) vs 13.5 (7.5) months in naive and experienced patients, respectively. TNFi-naive patients had greater persistence with their index TNFi (p=0.03) and were less likely to switch to another biologic (p=0.002) compared with TNFi-experienced patients. Provider-reported reasons for discontinuation included lack of effect (naive, 71%; experienced, 62%), side effects (10%; 23%), social reasons (6%; 3%), doing well (3%; 0%), and other (10%; 12%). Conclusions: In this real-world analysis of US patients with PsA, TNFi-experienced patients were more likely to discontinue and switch their index TNFi and had a shorter time to discontinuation compared with TNFi-naive patients. These results may help inform treatment decisions when selecting later lines of TNFi therapy in patients with PsA. Acknowledgements: This study was sponsored by Corrona, LLC. Disclosure of Interest: P. Mease Grant/research support from: AbbVie, Amgen, BMS, Celgene, Lilly, Novartis, Pfizer, UCB, Consultant for: AbbVie, Amgen, BMS, Celgene, Corrona, Genentech, Janssen, Lilly, Merck, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, BMS, Celgene, Genentech, Janssen, Pfizer, UCB, M. Liu Employee of: Corrona, LLC, B. Gershenson Employee of: University of Massachusetts Medical School, P. Hur Employee of: Novartis, J. Greenberg Shareholder of: Corrona, LLC, Consultant for: Eli Lilly, Genentech, Janssen, Novartis, Pfizer, Employee of: Corrona, LLC